Introduction to Critical and Creative Engagements with Petro-Media - Roehl, Emily; Jekanowski, Rachel Webb (Imaginations)

(untitled) (York University, 2022)
The production of oil is imbricated in financial and socio-political systems as well as ways of mediating the worlds in which we live. Like infrastructures used to transport fuel, audio-visual media and other forms of cultural production (museums, poetry, film, visual art) can serve as conduits for ideas about energy, identity, relationships to the nonhuman world, and history. This special issue of Imaginations on “Critical and Creative Engagements with Petro-Media” explores how media has been used to examine petroleum’s place within Canadian and American cultural landscapes as well as oil’s attendant socio-political and economic structures. Given our location on occupied Indigenous territories where we work as researchers and educators, we assert that energy developments are always already implicated within histories of white settlement in North America. Drawing on literary and film studies, energy humanities scholarship, critical museum studies, and a variety of creative and analytical research methods, the contributors to this issue theorize contemporary and historical practices of corporate petro-media alongside creative interventions to trace the interlacing of oil, media, and settler colonialism.